Bone Marrow-Derived Mesenchymal Stem Cells Repair Necrotic Pancreatic Tissue and Promote Angiogenesis by Secreting Cellular Growth Factors Involved in the SDF-1α/CXCR4 Axis in Rats - Daohai Qian; Jian Gong; Zhigang He; Jie Hua; Shengping Lin; Chenglei Xu; Hongbo Meng; Zhenshun Song (Stem Cells International)
Acute pancreatitis (AP), a common acute abdominal disease, 10%–20% of which can evolve into severe acute pancreatitis (SAP), is of significant morbidity and mortality. Bone marrow-derived mesenchymal stem cells (BMSCs) have been reported to have a potential therapeutic role on SAP, but the specific mechanism is unclear. Therefore, we conducted this experiment to shed light on the probable mechanism. We validated that SDF-1α significantly stimulated the expressions of VEGF, ANG-1, HGF, TGF-β, and CXCR4 in BMSCs, which were inhibited by its receptor agonist, AMD3100. The capacities of proliferation, migration, and repair of human umbilical vein endothelial cells were enhanced by BMSCs supernatant. Meanwhile, BMSCs supernatant could also promote angiogenesis, especially after the stimulation with SDF-1α. In vivo, the migration of BMSCs was regulated by SDF-1α/CXCR4 axis. Moreover, transplanted BMSCs could significantly alleviate SAP, reduce the systematic inflammation (TNF-α↓, IL-1β↓, IL-6↓, IL-4↑, IL-10↑, and TGF-β↑), and promote tissue repair and angiogenesis (VEGF↑, ANG-1↑, HGF↑, TGF-β↑, and CD31↑), compared with the SAP and anti-CXCR4 groups. Taken together, the results showed that BMSCs ameliorated SAP and the SDF-1α/CXCR4 axis was involved in the repair and regeneration process.